Implementation of Total Productive Maintenance with Overal Equipment Effectiveness (Oee) Method to Determine Maintenance Strategy for Digester Plant Machines (Case Study of PT. Toba Pulp Lestari, Tbk) - Juna Gelisman Edward (Trigin Publisher, 2021)
This study analyzed the implementation of Total Productive maintenace (TPM) on the machine Digester using Efectiveness Overall Equipment (OEE). Total Productive Maintenance (TPM) is to increase the productivity of the equipment and production equipment with an investment of treatments as necessary to prevent major losses occurred 6 (Six Big Losses). Six Big Losses are causing these losses are: Losses due to damage to the equipment (Breakdown Losses), losses due to the installation of equipment (Set-up and Adjustment losses), losses due to operate without load or paused (Idling and minorstoppages), losses due to the decline production speed (Speed Reduced losses), losses due to product defects in the process (Rework losses), the losses due to the low yield (Yield / Scrap losses).Based on the results of the calculation of OEE values in the machine Digester during the month of June 2015 - May 2015 obtained availability value=97.6% meet the standard JIPM by 90%, performance efficiency = 95.22% meet the standard JIPM by 95%, quality of rate = 97.00% this condition is not JIPM meet the standards of 99%, and the yield value of OEE = 90.20% is considered a world-class production. This score is a score that is suitable to serve as a long-term goal. The factor that has the greatest percentage of factor six big losses are idling and minor losses amounted to 50.98%, reduce speed losses of 23:59%, yield/scrap losses 14:49% set up and adjustment of 10:20%, Breakdown losses amounted to 0.78%. and to increase the value of OEE replacement of genuie spareparts are used to replace the damaged spare parts.